Towards a (Neuro-)Psychology of Art: Cues for Attention in Mesopotamian Art - Portuese, Ludovico (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
Psychology of art and neuroesthetics remain largely unknown to current scholarship in Mesopotamian art studies and only a few contributions have recently dealt with artefacts relying on these methods of investigation. The goal of this paper is to identify cues for the cognitive process of attention in ancient Mesopotamian art, aiming to find confirmation of their possible use by ancient Mesopotamian artists and audiences. A similar approach was used in ancient Greek art and this contribution represents an attempt to pave the way to open new perspectives for how ancient Near Eastern art can be analysed. The results show the universality of the audience’s attention towards art, probably connected with basic responses of cognitive processes.